EVALUATION OF SWELLING-SHRINKAGE IN LIME STABILIZED SOIL DUE TO THE ADDITION OF MATOS STABILIZER - Novi Suprianti (Journal of Applied Science, Engineering and Technology, 2023)
Bad soil properties such as high plasticity index values, high potential for swelling and shrinkage, and low shear strength are the problems encountered. To find out the swelling and shrinkage value of the soil, 2 stages of testing were carried out, namely testing the physical and mechanical properties of the soil and stabilizing it with additives in the form of 4% lime and 2%, 4% and 8% Matos soil stabilizer. The results of research on Capkala soil with a specific gravity value of 2.568, a liquid limit value of 51.444%, a plastic limit value of 29.507%, and an IP value of 21.937%. Then, based on sieving analysis, it shows that according to the AASHTO classification, Capkala soil is included in A-7-6, namely clay soil, while according to the USCS classification, it is included in the MH group, namely inorganic silt or fine sand, and according to the USDA classification, it includes silty clay. From the results of the disturbed soil swelling pressure test of 2.427 Kg/cm2 and included in the swelling potential low, while the 40% bentonite mixture obtained a swelling pressure result of 4.133 Kg/cm2 which was included in the swelling potential high. Meanwhile, the effect of adding Matos soil stabilizer to disturbed soil modified with 40% bentonite and Matos in the swelling pressure test resulted in the soil being included in the swelling potential medium. From the results of the disturbed soil FSI a value of 26.667% was obtained which has a moderate degree of development category. The effect of adding 40% bentonite to disturbed soil resulted in an increase of 45.455% in the category of high degree of development. Meanwhile, the effect of adding Matos soil stabilizer to disturbed soil modified with 40% bentonite in the free swelling index test included in the category of moderate degree of development.